Lymphoplasmocytic gastritis and duodenitis in a dog: Case report (Research, Society and Development, 2024)
Inflammatory Bowel Disease (IBD) or Chronic Inflammatory Enteropathy in dogs is characterized by chronic inflammatory alterations of the gastrointestinal tract, with a multifactorial etiology and challenging diagnosis. Among the most common causes of IBD are factors such as genetic predisposition, dysbiosis, increased gut permeability, and environmental factors. The clinical signs are nonspecific, recurrent, or persistent, including vomiting, diarrhea, weight loss, and appetite alterations for more than three weeks. Diagnosis is usually based on the exclusion of differential pathologies, anamnesis, and complementary exams. The treatment may involves dietary modification and medications such as corticosteroids, immunosuppressants, antibiotics, and supportive therapy with nutraceuticals. The prognosis of the disease depends on the type of enteropathy and its severity. This study aims to report the process of clinical investigation regarding a case of hyperplastic gastritis and erosive duodenitis lymphoplasmacytics, presented in a seven-year-old male Dachshund with a clinical history of chronic diarrhea and sporadic bilious vomiting. The methodology used in this article refers to a descriptive observational study of the case report type. The investigation of clinical signs involved making a diagnosis by exclusion, and suggesting a definitive diagnosis. Proper treatment and prognosis for IBD were initiated. Currently, the canine remains under treatment and stable.